Edukasi Gizi bagi Balita Usia 1-3 Tahun untuk Peningkatan Pengetahuan Ibu Balita Gizi Kurang di Gonggang Poncol Magetan - Rizky Tri Demarwan; Indah Azhari; Nabila Senja; Fatan Fakihardi (Health Community Engagement, 2025)
The issue of undernutrition among toddlers aged 1–3 years in Gonggang Village, Magetan Regency, remains a significant challenge that requires a collaborative intervention. One contributing factor is the lack of understanding among mothers about the principles of appropriate supplementary feeding and the limited use of local food resources. This program aims to improve the knowledge and skills of mothers in preparing and processing nutritious supplementary feeding menus based on local food ingredients through nutrition education and training in making "Nugget Banduka" (nuggets made from milkfish, tofu, and katuk leaves). The activity was carried out in three main stages: preparation, implementation, and evaluation, using interactive lectures, leaflet- and visual-based counseling, and live demonstrations. Evaluation through pre- and post-tests showed a significant increase in the participants' knowledge. In addition to improving children's nutritional quality, the program promotes family self-reliance in nutrition fulfillment and supports the use of local food potential. These results indicate that an applicable educational approach can be an effective strategy to enhance nutrition literacy and feeding practices for toddlers at the household level